Non-conscious errors in the control of dynamic events synchronized with heartbeats: A new challenge for human reliability study. (September 2020) - Vanderhaegen, F.; Wolff, M.; Mollard, R.
Highlights: A methodology to study the impact of the synchronization of events with heartbeats. The reduction of alarm detection ability is unconscious. This reduction increases when events occur synchronously with heartbeats. Hypotheses are validated by an experimental protocol with 27 subjects. Abstract: This paper studies the synchronization between dynamic events with heartbeats and its impact on non-conscious errors in the control of dynamic events. It proposes a methodology to compare two groups of subjects: a group for which alarms are synchronized with the heartbeats of the subjects and a group for which they are not. Quantitative and subjective data were recorded during four experimental phases from a low level to a high level of workload. Results showed that there was a significant impact of such a synchronization of events with heartbeat: people produced more errors when this synchronization was present and they were not really conscious about the disruption of their abilities. This study is very promising and shows the interest of developing future on-line or off-line human reliability assessment methods based on unsafe behaviors associated with this synchronization.